Effects of the Problem-Based Learning Model Assisted by Mind Mapping on the Science Learning Outcomes of Junior High School Students - Agustina, Putri; Arjunani, Rusmalistia Intan; Astuti, Rina; Agustina, Lina; Saputra, Alanindra (Universitas Negeri Jakarta, 2025)
Science learning is an effort to discover scientific truths through a series of thought processes. The demands of 21st-century science learning are learning that develops students' thinking skills. One learning model that is expected to train students' thinking skills is problem-based learning (PBL). This research aims to analyze the influence of the PBL learning model assisted by mind mapping on the science learning outcomes of class VII students at SMP Muhammadiyah 8 Surakarta for the 2022/2023 academic year. This research is a quasi-experimental research with a non-equivalent control group design. Samples were taken randomly, with 1 class as the control class and 1 class as the experimental class. The learning outcomes analyzed include cognitive, affective, and psychomotor learning outcomes. Data analysis was carried out using an independent sample t-test. Based on the research and data analysis results, there is a significant influence of the application of the PBL learning model assisted by mind mapping on students' science learning outcomes.